MOBILE ROBOT - ABU KASSIM, ABU MASNUR (Universiti Teknologi Petronas, 2004)
The essential components for a mobile robot include environment sensors, navigational intelligence and actuators (wheels or legs). The mobile robot to be developed in this project incorporates ultrasonic proximity sensors input devices as environment sensors and two motors (which control the wheels) as actuators. The main goal of this mobile robot is to avoid collisions with obstacles or walls and plan its paths around them for subsequent runs. A transmitter-receiver pair is used for the ultrasonic sensor circuitry. The transmitter mainly consists of a 555 timer and is controlled by an external device (microcontroller) to initiate pinging sequences. The receiver is primarily made up of LM741 Op-Amp, LM567tone decoder, and LM311 comparator. The LM741 is used to amplify the received signal while the LM567 is used to filter and detect only the preset frequency. The LM311 comparator is used to minimize false triggering emanating from power surges in the supply current. An H-bridge circuit is used to control the motors' forward/reverse motion via its 2 bit binary inputs at its strobes. The H-bridge circuit utilizes Darlington-Pair transistors and diodes to control the forward/reverse current flow to the motor. A PIC16F84 microcontroller is used as the brain of the mobile robot. The main function of the microcontroller is to initiate ping sequences to the ultrasonic transmitter, measure the time for the ping echo to return, and decide to move forward, turn or reverse the robot accordingly. Extended functions of the microcontroller is to create a 2Dterrain map, and plan its path to any specified target point. These are to be achieved by Voronoi Diagram or Delaunay Triangulation method for mapping, and a combination of one or more of the Dijkstra, Bellman, Ford, Moore, Johnson, Floyd-Warshal, or A* algorithms for best path calculation. In some parts of the project especially the intelligent navigation algorithms, the author encountered many new ideas and theories which the author cannot fully understand. It is hoped that future projects will emphasis on these areas.